A Combination of HHO and BEI Techniques for Frequency Control in Renewable-Dominated Microgrids: Towards Advancing Sustainable Development - Elnaggar, Mohamed F. (International Journal of Robotics and Control Systems, 2025)
To address the rising need for resilient and eco-friendly power systems, this research presents an intelligent load frequency control (LFC) framework specifically designed for hybrid microgrids with significant renewable energy integration and variable operational dynamics. The proposed control scheme leverages the Harris Hawks Optimization (HHO) algorithm in conjunction with a Balloon Effect (BE) adaptation mechanism, enabling real-time tuning of controller parameters in response to system fluctuations and disturbances. The simulation model encompasses a diverse hybrid microgrid configuration, comprising PV arrays, a diesel generator, and time-varying load profiles. Performance assessments were conducted across three operating modes: diesel-alone supply, coordinated diesel-PV operation, and a high-renewable scenario incorporating uncertainties in system inertia, damping, and droop. In all tested cases, the HHO + BE controller demonstrated superior behavior compared to standard optimization techniques like GTO, SCA, and WOA, exhibiting quicker stabilization, smaller frequency deviations (down to ±0.18 Hz), and minimized control actions. Overall, this study underscores the adaptability and reliability of the HHO + BE control approach for maintaining frequency stability in modern, low-inertia microgrids. The results offer compelling evidence of its effectiveness in real-time applications, particularly in environments increasingly dominated by fluctuating renewable energy sources and uncertain operating conditions.